Reformasi Transportasi Sultra: Maju, Aman Sejahtera dan Religius: (Kajian Kritis terhadap Visi dan Misi Gubernur Sulawesi Tenggara Tahun 2025-2030) - Syaiful Syaiful; Maudhy Satyadharma (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
Transportation development is a key foundation for increasing economic growth, regional connectivity, and the quality of public services. In Southeast Sulawesi, Governor Andi Sumangerukka's vision of "Advanced, Safe, Prosperous, and Religious" demands a transportation transformation that focuses not only on physical development but also on governance, technology, sustainability, and the socio-cultural values ​​of the community. This article presents a critical review of this vision and mission by examining the readiness of the transportation sector, the role of the Provincial Transportation Agency, the opportunities and challenges of transformation, and policy recommendations. This study employed a qualitative approach. The research activities were conducted at several transportation infrastructure facilities under the jurisdiction of the Southeast Sulawesi Provincial Transportation Agency for two months, from September to October 2025. The study shows that although the development direction reflects the strategic needs of the archipelago, significant challenges remain, such as inter-island connectivity, gaps in transportation services, data digitization, and a culture of safety. Pentahelix-based, ecological, and technology-based transportation reforms are key to achieving the regional development vision.